Peran Pemerintah dalam Ekosistem Startup Sosial : Kajian Ekonomi Publik terhadap Insentif dan Hambatan Fiskal - Bagas Saputra; Jauzari Helmi; M. Rizky Indrawan Saputra; W Pangestoeti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the role of government in the social startup ecosystem in Indonesia, focusing on fiscal incentives and barriers. The rapid growth of startups has changed lifestyles, but many social startups face challenges due to inadequate government support and fiscal policies. This study uses a qualitative approach, analyzing secondary data from government documents and academic literature. Findings show that fiscal incentives, such as tax breaks, significantly increase operational capacity and innovation among social startups. However, complex regulations and high tax burdens remain substantial barriers. This study recommends policy reforms to create an enabling environment for social startups, contributing to inclusive and sustainable economic development.